Prevalence of Swine Gastrointestinal Parasites in Nyagatare District, Rwanda - M. Tumusiime; P. Ntampaka; F. Niragire; T. Sindikubwabo; F. Habineza (Journal of Parasitology Research)
While pig farming has been growing rapidly in Rwanda, its potential contribution to the prevalence of zoonotic infections is not well known. Pig production is usually affected by gastrointestinal parasites, some of which are zoonotic and can threaten human health. The knowledge about the status of such infections is essential for policy decisions and interventions. We aimed to investigate the prevalence of swine gastrointestinal parasites in Nyagatare district, Rwanda. A cross-sectional study involved collecting 104 faecal samples from apparently healthy pigs. The floatation technique was used to identify the parasites and frequency distribution analysis, and Pearson chi-square tests of association were conducted for this study data. Overall, the prevalence of swine gastrointestinal parasites was 84.6%, and the predominant species were Strongyle-type helminths representing 70.2%, followed by coccidia (55.8%), Strongyloides ransomi (39.4%), and Ascaris suum (10.6%). Of all parasitized pigs (n=88), 84.1% developed coinfections involving 2, 3, or 4 different parasite species. The results showed a statistically significant correlation between the location of pigs and parasitic infections and that some prevalent parasites are zoonotic. Interventions among pig farmers in Nyagatare should aim to improve awareness and to provide information on the negative impacts of swine gastrointestinal parasites on pig production and human health.